Neuroactive steroids, nociception and neuropathic pain: a flashback to go forward - Coronel, Maria Florencia (2016)
The present review discusses the potential role of neurosteroids / neuroactive steroids in the regulation of nociceptive and neuropathic pain, and recapitulates the current knowledge on the main mechanisms involved in the reduction of pain, especially those occurring at the dorsal horn of the spinal cord, a crucial site for nociceptive processing. We will make special focus on progesterone and its derivative allopregnanolone, which have been shown to exert remarkable actions in order to prevent or reverse the maladaptive changes and pain behaviors that arise after nervous system damage in various experimental neuropathic conditions.